Occurrence and Fate of Ultramicrobacteria in a Full-Scale Drinking Water Treatment Plant - Liu, Jie; Zhao, Renxin; Zhang, Jiayu; Zhang, Guijuan; Yu, Ke; Li, Xiaoyan; Li, Bing (Frontiers in Microbiology, 2018)
Ultramicrobacteria (UMB) are omnipresent and numerically dominate in freshwater, as microbes can present in drinking water systems, however, the UMB communities that occur and their removal behaviors remain poorly characterized in drinking water treatment plants (DWTPs). To gain insights into these issues, we profiled bacterial cell density, community structure and functions of UMB and their counterpart large bacteria (LB) using flow cytometry and filtration paired with 16S rRNA gene high-throughput sequencing in a full-scale DWTP. Contrary to the reduction of bacterial density and diversity, the proportion of UMB in the total bacteria community increased as the drinking water treatment process progressed, and biological activated carbon facilitated bacterial growth. Moreover, UMB were less diverse than LB, and their community structure and predicted functions were significantly different. In the DWTP, UMB indicator taxa were mainly affiliated with α/β/γ-Proteobacteria, Deinococcus-Thermus, Firmicutes, Acidobacteria, and Dependentiae. In particular, the exclusive clustering of UMB at the phylum level, e.g., Parcubacteria, Elusimicrobia, and Saccharibacteria, confirmed the fact that the ultra-small size of UMB is a naturally and evolutionarily conserved trait. Additionally, the streamlined genome could be connected to UMB, such as candidate phyla radiation (CPR) bacteria, following a symbiotic or parasitic lifestyle, which then leads to the observed high connectedness, i.e., non-random intra-taxa co-occurrence patterns within UMB. Functional prediction analysis revealed that environmental information processing and DNA replication and repair likely contribute to the higher resistance of UMB to drinking water treatment processes in comparison to LB. Overall, the study provides valuable insights into the occurrence and fate of UMB regarding community structure, phylogenetic characteristics and potential functions in a full-scale DWTP, and it is a useful reference for beneficial manipulation of the drinking water microbiome.